Educação do corpo e a prática corporal do crossfit: a cultura fitness como temática de análise - Abreu, Jerlane Santos (2021)
This dissertation aims to reflect on body education concerned with crossfit practices through the analysis of fitness culture undergone at a gym called "Crossfit Aju" in the city of AracajuSE. The crossfit is brought to this study in order to think about political and aesthetic issues through that body practice. Thus, the concept of “body education” is central to our study. In this regard, building up an object around the body to be analyzed implies considering that it can only exist when discourses inherent to its practices are considered. Questioning the body by considering its practices implies studying it through the bias of the policy in which it is inscribed. Body practices are shaped according to the needs of its uses, in a spatial and timing dynamic, which, consequently, implies constant variation of its different meanings. This research is based on the interest of a Master Program in Education, which is justified as an investigation of a broad object in the possibility of inquiry, because the crossfit allows a series of assumptions to think about body education in non-formal scopes, as well as a cultural pedagogy that directly influences the subject's educational act. Given the methodological choices, this study is characterized as a fieldwork based on a qualitative approach that assumes an exploratory nature as type of research. Data production took place in two occasions. In the first moment of the research, we used direct observation as instrument for previous contact as a crossfit participant-practitioner. Then, the second moment of the research took place through field exploration aimed at data collection through the following tools: field diary, 23 semistructured interviews with open questionnaires applied to teachers and students. Other instruments for data collection were intensive direct observation and media product analysis: Instagram. Based on this and inspired by Foucault's tools, we were led to define data analysis from the perspective of discourse analysis. Therefore, it was possible to identify a series of discursive practices that trigger ways of being that subject, objectify and subjectify identities, bodies and subjects. In this way, we allocated this empiricism and organized the results in six sections, from which we found unanimity in motivational discourses as an influential technique regarding body education, which produces and conducts desires through the accountability of self-government. We also recognized Crossfit Aju as a contemporary biopolitical device, as well as the maintenance of disciplinary society and the continuity of the propagation of ideal body patterns under new modes, subjects and behaviors. However, some analytics were also considered as a possible act of resisting the subjection that creates unique bodies, interpreted through some actions and discourses which in a certain way rejects the ideals that lead to conduct. Thus, small libertarian acts were registered, once only two interviewees presented elements for the refusal of normative models by developing well-founded criticisms concerning body aesthetics are not restricted, but in a creative way differently from the so called “Crossfiteira” identity.